DEVELOPING DIGITAL MULTIMEDIA OF HUMAN ANATOMY AND PHYSIOLOGY MATERIAL BASED ON STEM EDUCATION - Hidayati, Nuril; Irmawati, Farizha (University of Muhammadiyah Malang, 2019)
The development of multimedia based on science, technology, engineering, and mathematics (STEM) to empower students critical thinking skills has not been optimally carried out. The purpose of this research was to develop multimedia of human anatomy and physiology material based on STEM which improve students? critical thinking skills. This research and development (R&D) used 4D Thiagarajan development model which consisted of define, design, develop, and disseminate. The instruments used were interview guidelines, observation sheets, questionnaires, and test. The data obtained consisted of quantitative and qualitative data. The quantitative data was obtained from the test results and the assessments of respondents using a Likert scale, while the qualitative data in the form of experts recommendations. The results showed that the media developed were classified as valid with the scores were 96.89% (media aspects), 97.53% (usefulness), and 85.22% (readability). Furthermore, the prerequisite test results showed that the data are spread normally (p>0.05) and homogeneously (p>0.05) so that the ANACOVA test is continued. The ANACOVA test results showed that students' critical thinking skills taught with multimedia were significantly difference (sig <0.05).This study recommends the use of multimedia in learning human anatomy and physiology.